The Voice of Foreign Direct Investment : Foreign Investor Policy Preferences and Experiences in Developing Countries - Saurav, Abhishek; Kuo, Ryan (World Bank, Washington, DC, 2020)
This paper provides insights to inform government efforts to attract and retain foreign direct investment, by analyzing the results of a survey of more than 2,400 affiliates of multinational enterprises across 10 middle-income countries. The paper explores corporate perspectives and decision-making on countries’ legal and regulatory environments, political risk, and investment promotion activities. The survey finds that a business-friendly policy environment is critical to multinational enterprises’ investment decisions, confirming the importance of removing regulatory barriers to foreign direct investment (particularly approval processes), lowering political risks, and having investment promotion agencies. The survey results also show that investors are heterogeneous, with affiliates’ sectors, trading behaviors, sizes, ages, source countries, and foreign ownership levels affecting their perceptions of and sensitivity to various policy factors. Thus, policy makers should tailor their policy efforts to the needs of priority investor segments. Notably, the analysis consistently finds variation based on the extent to which affiliates import their inputs, suggesting that this relatively understudied topic deserves increased research and policy attention.